CD206+ Cell Number Differentiates Influenza A (H1N1)pdm09 from Seasonal Influenza A Virus in Fatal Cases - Rodriguez-Ramirez, Heidi G.; Salinas-Carmona, Mario C.; Barboza-Quintana, Oralia; Melo-de la Garza, Americo; Ceceñas-Falcon, Luis Angel; Rangel-Martinez, Lilia M.; Rosas-Taraco, Adrian G. (Mediators of Inflammation, 2014)
In 2009, a new influenza A (H1N1) virus affected many persons around the world. There is an urgent need for finding biomarkers to distinguish between influenza A (H1N1)pdm09 and seasonal influenza virus. We investigated these possible biomarkers in the lung of fatal cases of confirmed influenza A (H1N1)pdm09. Cytokines (inflammatory and anti-inflammatory) and cellular markers (macrophages and lymphocytes subpopulation markers) were analyzed in lung tissue from both influenza A (H1N1)pdm09 and seasonal influenza virus. High levels of IL-17, IFN-γ, and TNF-α positive cells were identical in lung tissue from the influenza A (H1N1)pdm09 and seasonal cases when compared with healthy lung tissue (P<0.05). Increased IL-4+ cells, and CD4+ and CD14+ cells were also found in high levels in both influenza A (H1N1)pdm09 and seasonal influenza virus (P<0.05). Low levels of CD206+ cells (marker of alternatively activated macrophages marker in lung) were found in influenza A (H1N1)pdm09 when compared with seasonal influenza virus (P<0.05), and the ratio of CD206/CD14+ cells was 2.5-fold higher in seasonal and noninfluenza group compared with influenza A (H1N1)pdm09 (P<0.05). In conclusion, CD206+ cells differentiate between influenza A (H1N1)pdm09 and seasonal influenza virus in lung tissue of fatal cases.